2015
DOI: 10.5539/elt.v8n12p63
|View full text |Cite
|
Sign up to set email alerts
|

An EMI Pedagogy That Facilitates Students' Learning

Abstract: In recent decades, increasing numbers of EMI (English as Medium of Instructions) courses have been added to university course offerings in countries where English is not the first language, as a way of supporting university internalization and addressing the global status of English. However, some studies argue that EMI courses might affect the overall learning of course content because of students' poor lecture comprehension and passive engagement in class. In order to facilitate student engagement and improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
2
11
1
Order By: Relevance
“…With regards to the quantitative perspectives of course attitudes and satisfaction, the overall scores for the two semesters were computed as slightly high, which is typical for many elective EMI courses in Taiwan [ 119 ], regardless of being blended or not. This is actually due to the elective nature of the course.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the quantitative perspectives of course attitudes and satisfaction, the overall scores for the two semesters were computed as slightly high, which is typical for many elective EMI courses in Taiwan [ 119 ], regardless of being blended or not. This is actually due to the elective nature of the course.…”
Section: Discussionmentioning
confidence: 99%
“…In the specific EMI context that is the focus of this chapter, teaching issues such as diverse student backgrounds and large class sizes can complicate how well students' engagement with learning activities and their interactions with teachers and fellow students may be facilitated and achieved. In EMI literature ensuring student engagement by increasing interaction has been a key concern (e.g., Chuang, 2015;Hsieh et al, 2007;Huang, 2014). These studies pointed out that the choice by EMI teachers of whether to incorporate interactive tasks (e.g., group discussions) in their classes is often related to factors such as discipline, course type, and class size.…”
Section: Inclusion Of Business Casesmentioning
confidence: 99%
“…Previous studies related to EMI in higher education have pointed out that subject teachers adopting English as the instructional language often encounter problems in capturing the attention of demotivated students. Interactive activities are therefore used as instructional approaches to promote student participation and to enhance the effectiveness of EMI teaching and learning (e.g., Chuang, 2015;Hsieh et al, 2007;Huang, 2014;. When proposing suggestions on how future EMI classroom practices can be improved, these studies often included the introduction of interactive tasks or group activities that promote cooperation among students.…”
Section: Research On Interaction In the Emi Classroommentioning
confidence: 99%
“…Several pieces of research have shown that effective lecturing pedagogy, especially in terms of lecturing behavior and approach, can contribute to EMI students' comprehensibility, motivation, engagement, and attention (Chuang, 2015;Flowerdew, 1994;Klaassen, 2001;Suviniitty, 2010). perceived as making comprehension easier, such as systematic presentation of information, summarizing lecture points, lecturer's responses to students' questions, lecturer initiating interaction with students during the lecture, and repetition of main points.…”
Section: Emi Lecturing Pedagogymentioning
confidence: 99%